Review of Superannuation Benefit Programs in Sri Lanka - World Bank (Washington, DC, 2013)
This report examines the current system of old age income security in Sri Lanka to determine whether it provides reasonable pension for retirees. It also explores the effects of the current system on labor market mobility and the fiscal deficit and looks at the potential for establishing greater demand for debt, particularly long-term debt, and equity securities through the strengthening of contractual savings. The focus of this note has been to review the formal systems of retirement savings provision currently in place in Sri Lanka, particularly from the perspective of cost effectiveness and administrative efficiency, and to ascertain policy options available to the government of Sri Lanka. The report outlines key objectives which would address material shortcomings in the present system, proposes potential reform strategy components, and explores measures which might assist in achieving these goals.